(untitled) (Global Journal of Science Frontier Research, 2023)
This paper studies hat air crash would be caused by the difference of pressures between outside and inside of passenger s cargo Such difference of pressures can break the window or door and thus make the plane to crash In order to calculate the pressure outside passenger s cargo this paper set up and solves the solution of three type equations A w T eq B w - P eq and C J - P eq The A type is the base It states that the derivative of wind speed respect to time proportions to the derivative of temperature respect to track space The A s solution obtained by method of separating variables has been checked by weather forecasting by dimensional check and by other model check The solutions of B and C can be obtained directly from A Missing plane MH370 has been used as an example to show the calculation of pressure outside the passenger s cargo This paper would be referenced to pilot administrator engineer scientist teacher and student